2017
DOI: 10.3390/foods6010005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Availability and Antioxidant Capacity of Maillard Compounds Present in Bread Crust: Studies in Caco-2 Cells

Abstract: Bread crust is one of the major contributors to the intake of Maillard reaction products (MRP). MRP improve the organoleptic properties of foods and can provide biological actions such as antioxidant properties. The transport and availability of Amadori compounds (measured as furosine) and hydroxymethylfurfural (HMF)—early and intermediary MRP—from enzymatically digested bread crust (BC) and from its soluble low-molecular weight (LMW) and high-molecular weight (HMW) fractions were investigated in the Caco-2 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
1
3
0
1
Order By: Relevance
“…FRAP activity (Figure 5) was significantly higher in the colonic fermentation fractions of both CBM and SBM compared with the GI fraction. Other authors have pointed out that the fraction of melanoidins that crosses through the intestinal barrier still presents antioxidant capacity, in addition of being able to act at the cellular level as an antioxidant defense against the production of reactive oxygen species [33]. Therefore, we confirmed that GI and F bioaccessible melanoidins that have crossed the intestinal barrier remain with a high antioxidant activity that can provide beneficial effects at the cellular level.…”
Section: Resultssupporting
confidence: 84%
“…FRAP activity (Figure 5) was significantly higher in the colonic fermentation fractions of both CBM and SBM compared with the GI fraction. Other authors have pointed out that the fraction of melanoidins that crosses through the intestinal barrier still presents antioxidant capacity, in addition of being able to act at the cellular level as an antioxidant defense against the production of reactive oxygen species [33]. Therefore, we confirmed that GI and F bioaccessible melanoidins that have crossed the intestinal barrier remain with a high antioxidant activity that can provide beneficial effects at the cellular level.…”
Section: Resultssupporting
confidence: 84%
“…Accordingly, many different biological effects have been attributed to melanoidins. They can behave as prebiotic (Helou et al, 2015;Jiménez-Zamora, Pastoriza & Rufián-Henares, 2015), they have an important antioxidant capacity (Delgado-Andrade & Morales, 2005;Carvalho, Correia, Lopes, & Guido, 2014;de la Cueva, Seiquer, Mesías, Rufián-Henares, & Delgado-Andrade, 2017) and antimicrobial activity (Rufián-Henares & de la Cueva, 2009), and they can possess inhibitory activity against angiotensin I-converting enzyme .…”
Section: Introductionmentioning
confidence: 99%
“…Salah satu contoh MRPs (Maillard Reaction Product) adalah melanoidin yang berperan sebagai warna coklat pada makanan selain itu senyawa ini juga memiliki aktivitas antioksidan (Rufián-Henares & Morales, 2007) yang dapat diukur pada panjang gelombang 420 nm (de la Cueva et al, 2017).…”
Section: Hasil Dan Pembahasan Persen Inhibisiunclassified